P057 Prevalence of poor sleep in First Nations peoples across the globe: A systematic review. (9th November 2022) - Jabran, D; Potia, A; Smith, S; Solomon, S; Fernandez, D; Fatima, Y
Abstract: This review aims to collate and assess the extant literature on the prevalence of sleep issues among First Nations peoples across the globe. A systematic literature search, was conducted across key academic databases and grey literature sources to retrieve studies published until November 2021. Studies offering quantitative data on sleep issues in First Nations Peoples were included. The NIH Quality Assessment Tool was used to assess the methodological quality and an adapted version of the Indigenous Quality Appraisal tool was used to evaluate First Nations' engagement in research. Results: A total of 65 studies, (28 longitudinal, 37 cross-sectional) met the inclusion criteria for this review. The included evidence indicated that the First Nations Australians reported night-time awakenings (22%), severe daytime sleepiness (27%), short sleep duration (35%) and long sleep duration (41%). The Māori population from New Zealand consistently reported insufficient sleep (36%) and short sleep duration (28.6%). The First Nations Americans / Alaska Native populations reported insomnia (25% to 33%) and insufficient sleep (15% to 40%). The Cree First Nations from Canada had a higher prevalence of insomnia (38.5%) and sleep deprivation (25% to 40%). Most studies scored "quality" in quality assessment. However, First Nations' engagement in research could not be adequately assessed due to limited information. The review findings highlight that a significant proportion of First Nations peoples are experiencing poor sleep. Considering the established link between poor sleep and adverse health outcomes, sleep health equity in First Nations communities should be a high priority for service providers and policymakers.